SECURITY CHALLENGES AND SUSTAINABLE ECO/RURAL TOURISM DEVELOPMENT IN NIGERIA: EXAMPLES OF IDANRE HILLS AND OWU FALLS - Tunde; Afolabi Monisola; Omojola; Peter Oluwatosin (Malaysian Journal of Tropical Geography (MJTG), 2023)
Eco and rural tourism are keys to sustainable economic development in most developing countries, including Nigeria. In Nigeria, security challenges have threatened eco and rural tourism, impeding economic development. This paper examines the effects of national insecurity on tourism development in Idanre (Idanre Hills) and Owu-Isin (Owu falls) in Nigeria. It identified types of insecurity issues common in the study areas; examined causes of insecurity; determined the effects of insecurity in relation to patronage; and assessed the coping strategies. A total of one hundred residents of the host communities were randomly sampled with copies of the questionnaire, while tourist guides and tourists were interviewed. Tables, frequencies, Chi-square and trend analysis, were employed to analyze the gathered data. Findings revealed the common insecurity challenges in the host communities, including abduction and farmer/herders clashes. Causes include neglect of the people (82.0%) and poverty (74.0%). Effects identified include: giving the country a bad image and low patronage at the tourist sites. Coping strategies include using detective equipment and CCTV camera, education and community policing. It can therefore be concluded that eco and rural tourism hold promise for sustainable development of the host communities if security is guaranteed, and basic social amenities provided especially at Owu falls.